Removal of Phosphate from Wastewater by Steel Slag with High Calcium Oxide Column Filter System; Efficiencies and Mechanisms study - Ahmad, Siti Zu Nurain; Al-Gheethi, Adel; Hamdan, Rafidah; Othman, Norzila; Alkhadher, Sadeq (Research Gate, 2020)
Background: The discharge of wastewater with heavy loads of phosphorus leads to the eutrophication in natural water systems. The current work investigated the removal of phosphorus from synthetic wastewater through the medium of a slag filtration system with a high content of CaO was selected as the filter media (HCa) and subjected to treatment in the electric arc furnace (EAF). The pH, point of zero charge (PZC) and XRF of the HCa filter medium was studied. The removal of phosphorus was investigated in a designed vertical column filters in aerated HCa (AEF) and unaerated HCa (UEF) systems. FTIR, XRD and SEM-EDX analyses was implemented for studying the microstructure of HCa. Results: The results of XRF revealed that CaO ranged from 20.2–49.5%. The PZC for the HCa filter was recorded at pH 17.75. The highest efficiencies recorded were 94.65 ± 3.46% and 96.13 ± 2.75% at pH 3 and 93.70 ± 2.59% and 97.15 ± 1.59% at pH 5 for AEF and UEF, respectively. These findings indicated that AEF performed greater removal than UEF systems might due to presence high Ca concentration in AEF, which plays an important role in the process of phosphorus removal. The main elements on the surface of HCa included oxygen, carbon, magnesium, calcium, aluminium and silicon. XRD analysis indicated that the precipitation of orthophosphate as calcium and Ca-phosphates was the removal mechanism, which was confirmed using the FT-IR analysis. Conclusion: These findings demonstrated the efficiency of HCa in removing phosphorus from wastewater.